2017
DOI: 10.1093/brain/awx171
|View full text |Cite
|
Sign up to set email alerts
|

Distinct 18F-AV-1451 tau PET retention patterns in early- and late-onset Alzheimer’s disease

Abstract: Patients with Alzheimer's disease can present with different clinical phenotypes. Individuals with late-onset Alzheimer's disease (>65 years) typically present with medial temporal lobe neurodegeneration and predominantly amnestic symptomatology, while patients with early-onset Alzheimer's disease (<65 years) exhibit greater neocortical involvement associated with a clinical presentation including dyspraxia, executive dysfunction, or visuospatial impairment. We recruited 20 patients with early-onset Alzheimer'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
135
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
3

Relationship

4
6

Authors

Journals

citations
Cited by 155 publications
(156 citation statements)
references
References 24 publications
19
135
1
1
Order By: Relevance
“…For voxel‐wise analyses, [ 18 F]flortaucipir images were warped into the Montreal Neurological Institute standard space using the nonlinear transformation calculated by normalizing the T1‐weighted MRI scan to the Montreal Neurological Institute 152 1 × 1 × 1 mm 3 template with Advanced Normalization ToolS. Before voxel‐wise analyses, images were smoothed with an 8‐mm full width at half maximum Gaussian kernel …”
Section: Methodsmentioning
confidence: 99%
“…For voxel‐wise analyses, [ 18 F]flortaucipir images were warped into the Montreal Neurological Institute standard space using the nonlinear transformation calculated by normalizing the T1‐weighted MRI scan to the Montreal Neurological Institute 152 1 × 1 × 1 mm 3 template with Advanced Normalization ToolS. Before voxel‐wise analyses, images were smoothed with an 8‐mm full width at half maximum Gaussian kernel …”
Section: Methodsmentioning
confidence: 99%
“…The ability to assess and monitor pathological brain changes in the preclinical and clinical stages of AD is limited, especially in the asymptomatic phase of the disease. A current focus of AD biomarker research is on measurement of brain amyloid-β and tau protein dynamics as assessed by radiolabeled tracers to aggregated forms of these proteins, in addition to established measurements of amyloid-β and tau protein levels in cerebrospinal fluid (CSF) 50,51 . Fluid biomarkers of neurodegeneration are also in development 52 .…”
Section: M4 Astrocyte/microglial Metabolism Module Proteins Can Be Mementioning
confidence: 99%
“…Tau aggregations into neurofibrillary tangles are a hallmark pathological feature of Alzheimer's disease (Braak and Braak, 1991), and are consistently shown to correlate more strongly with cognitive functions than Amyloid-β plaques (Nelson et al, 2012;Rolstad et al, 2013). Excitingly, the advent of PET ligands that bind to Tau aggregations, such as 18 F-Flortaucipir (Chien et al, 2013), allows us to investigate the relationship between the spatial distribution of Tau in vivo throughout the course of Alzheimer's disease (James et al, 2015;LaPoint et al, 2017;Lowe et al, 2017;Schöll et al, 2017;Xia et al, 2017), and has been shown to relate to clinical symptoms associated with atypical AD such as Logopenic Aphasia and Posterior Cortical Atrophy (Ossenkoppele et al, 2016).…”
Section: Association With Tau Pathologymentioning
confidence: 99%